Bosnia and Herzegovina : Second Review Under the Stand-By Arrangement and Requests for Waivers of Applicability and Modification of Performance Criteria -Staff Report; Press Release; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2013)
The economy of Bosnia and Herzegovina, which is strongly connected to Europe through trade and financial channels, continues to pay a high price for the tough conditions in the area. The paper discuss that, following low demand in its trading partners, exports slumped in 2012 by 7.5 percent, dragging the economy to an export-led recession that resulted in a contraction of economic activity by 0.7 percent. The share of government spending in GDP fell by almost a percentage point, offsetting completely the automatic stabilizers.